خصائص رسوم التلاميذ ذوي صعوبات التعلم ما بين سن "7-9" سنوات طبقا لما يقابلها على تقسيم فيكتور لونفيلد لمراحل نمو التعبير الفني عند الأطفال العاديين - الثقفي، عبدالله بن دخيل الله عوض (جامعة الزقازيق - كلية علوم الإعاقة والتأهيل, 2017)
يهتم هذا البحث بالمقارنة بين خصائص رسوم الأطفال ذوي صعوبات التعلم (صعوبات تعلم الرياضيات، صعوبات تعلم القراءة، وصعوبات تعلم الرياضيات والقراءة معاً) وبين رسومات الأطفال العادين بين سن (7-9) سنوات، مستخدمة تقسيم فيكتور لونفيلد لمراحل نمو التعبير الفني لدى الأطفال كمقياس لتلك المقارنة، وقد أستخدم في هذا البحث المنهج الوصفي، وقد أعد الباحث أداة بحثية لتحليل رسوم الأطفال في عينة البحث لكي يتمكن من اختيار فرضية البحث. وقد خلصت البحث إلى مجموعة من النتائج والتوصيات، ومن أهمها إثبات صحة فرضية البحث وهي: أنه توجد فروق ذات دلالة إحصائية بين خصائص رسوم التلاميذ ذوي صعوبات التعلم في سن (7-9) سنوات، وبين خصائص رسوم أقرانهم العاديين. This study deals with the comparison between characteristics of normal children’s drawings and characteristics of drawings done by children who struggle with mathematics, reading, and math and reading combined. The study used Victor Low enfeld division of the development alstages of children’s artistic expression. It used this division as a scale of comparison. The researcher used the descriptive style of comparative content analysis to achieve the objectives of the study. The researcher has also prepared a research tool for the analysis of children’s drawings in the research sample to be able to test the hypothesis. The study concluded with a set of results and recommendations. The most important of that is proof of research hypothesis, which is “there are statistically significant differences between characteristics of drawings done by children with the learning disabilities aged (7-9 years), and characteristics of children’s drawings depending on Victor Lowenfeld division of the developmental stages of children’s artistic expression”.
Keywords: التعبير الفني -- الأطفال العاديين -- رسوم التلاميذ -- صعوبات التعلم